The Royal Divide - Exploring the impact of Megxit on the future of the British monarchy - Intveen, Julie; Bauer, Maike (Englisch betrifft uns)

The True Story of a Total Fake – Eine Untersuchung des didaktischen Potentials von Netflix‘ Inventing Anna - Intveen, Julie; Hohwiller, Peter (Fernsehserielles Erzählen im fächerübergreifenden Unterricht)

Fictions of Identity – A Didactic Exploration of TV Series - Intveen, Julie (15. Nachwuchstagung der Deutschen Gesellschaft für Fremdsprachenforschung (DGFF), Thema: Findungsphasen)

Fictions of Identity – A Didactic Approach to Serial Literacy - Intveen, Julie (Media Literacy in Language (Teacher) Education)

Chasing the American Dream: Chances and challenges of immigrant families – a media task - Intveen, Julie (Englisch betrifft uns)

Was heißt Überleben? Die Zweischneidigkeit eines ubiquitären Begriffs - Althoff, Sebastian (Berliner Debatte Initial)

Funnel control of linear systems with arbitrary relative degree under output measurement losses - Berger, Thomas; Lanza, Lukas (IMA Journal of Mathematical Control and Information,)

Edge-wise funnel output synchronization of heterogeneous agents with relative degree one - Lee, J. G.; Berger, Thomas; Trenn, S.; Shim, H. (Automatica)

Business Models for Cultural Event Platforms - A Taxonomy Approach - Althaus, Maike; Grieger, Nicole; Vorbohle, Christian; Müller, Michelle; Kundisch, Dennis (Proceedings of the 15th Mediterranean Conference on Information Systems (MCIS))

Energy-Efficient Rate Splitting for MIMO STAR-RIS-Assisted Broadcast Channels with I/Q Imbalance - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard (2023 31st European Signal Processing Conference (EUSIPCO))

SNR Maximization in Beyond Diagonal RIS-Assisted Single and Multiple Antenna Links - Santamaria, Ignacio; Soleymani, Mohammad; Jorswieck, Eduard; Gutiérrez, Jesús (IEEE Signal Processing Letters)
Keywords: Applied Mathematics; Electrical and Electronic Engineering; Signal Processing

Optimization of Rate-Splitting Multiple Access in Beyond Diagonal RIS-assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard; Clerckx, Bruno (IEEE Transactions on Wireless Communications)
Keywords: Applied Mathematics; Electrical and Electronic Engineering; Computer Science Applications

NOMA-Based Improper Signaling for Multicell MISO RIS-Assisted Broadcast Channels - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard; Rezvani, Sepehr (IEEE Transactions on Signal Processing)
Keywords: Electrical and Electronic Engineering; Signal Processing

Spectral and Energy Efficiency Maximization of MISO STAR-RIS-Assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard A. (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Interference Leakage Minimization in RIS-Assisted MIMO Interference Channels - Santamaria, Ignacio; Soleymani, Mohammad; Jorswieck, Eduard; Gutiérrez, Jesús (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Developing a deep canonical correlation-based technique for seizure prediction - Vieluf, Solveig; Hasija, Tanuj; Kuschel, Maurice; Reinsberger, Claus; Loddenkemper, Tobias (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

Geodesic-Based Relaxation For Deep Canonical Correlation Analysis - Kuschel, Maurice; Marrinan, Timothy; Hasija, Tanuj (2023 IEEE 33rd International Workshop on Machine Learning for Signal Processing (MLSP))

Online system identification and excitation for thermal monitoring of electric machines using machine learning and model predictive control - Gedlu, Emebet Gebeyehu; Wallscheid, Oliver; Böcker, Joachim; Nelles, Oliver (2023 IEEE 14th International Symposium on Diagnostics for Electrical Machines, Power Electronics and Drives (SDEMPED))

Die epistemische Gewalt KI-basierter Gesichtserkennung. Wie ein codierter Blick neue Formen der technologisierten Subalternität erschafft - Kostan, Anastassija (Bedeutung und Implikationen epistemischer Ungerechtigkeit)

Global smooth solutions in a three-dimensional cross-diffusive SIS epidemic model with saturated taxis at large densities - Tao, Youshan; Winkler, Michael (Evolution Equations and Control Theory)
Keywords: Applied Mathematics; Control and Optimization; Modeling and Simulation

A quantitative strong parabolic maximum principle and application to a taxis-type migration–consumption model involving signal-dependent degenerate diffusion - Winkler, Michael (Annales de l'Institut Henri Poincaré C, Analyse non linéaire)
Keywords: Mathematical Physics; Analysis; Applied Mathematics

Refined regularity analysis for a Keller-Segel-consumption system involving signal-dependent motilities - Li, Genglin; Winkler, Michael (Applicable Analysis)
Keywords: Applied Mathematics; Analysis

Small-signal solutions to a nonlocal cross-diffusion model for interaction of scroungers with rapidly diffusing foragers - Tao, Youshan; Winkler, Michael (Mathematical Models and Methods in Applied Sciences)
As a simplified version of a three-component taxis cascade model accounting for different migration strategies of two population groups in search of food, a two-component nonlocal nutrient taxis system is considered in a two-dimensional bounded convex domain with smooth boundary. For any given conveniently regular and biologically meaningful initial data, smallness conditions on the prescribed resource growth and on the initial nutrient signal concentration are identified which ensure the global existence of a global classical solution to the corresponding no-flux initial-boundary value problem. Moreover, under additional assumptions on the food production source these solutions are shown to be bounded, and to stabilize toward semi-trivial equilibria in the large time limit, respectively.
Keywords: Applied Mathematics; Modeling and Simulation

A critical exponent for blow-up in a two-dimensional chemotaxis-consumption system - Ahn, Jaewook; Winkler, Michael (Calculus of Variations and Partial Differential Equations)
Keywords: Applied Mathematics; Analysis

Analysis of a chemotaxis-SIS epidemic model with unbounded infection force - Tao, Youshan; Winkler, Michael (Nonlinear Analysis: Real World Applications)
Keywords: Applied Mathematics; Computational Mathematics; General Economics; Econometrics and Finance; General Engineering; General Medicine; Analysis

Relaxation in a Keller-Segel-consumption system involving signal-dependent motilities - Li, Genglin; Winkler, Michael (Communications in Mathematical Sciences)
Keywords: Applied Mathematics; General Mathematics

Global generalized solvability in a strongly degenerate taxis-type parabolic system modeling migration–consumption interaction - Winkler, Michael (Zeitschrift für angewandte Mathematik und Physik)
Abstract The parabolic problem $$\begin{aligned} \left\{ \begin{array}{l} u_t=\Delta \big (u\phi (v)\big ), \\ v_t=\Delta v-uv, \end{array} \right. \end{aligned}$$ u t = Δ ( u ϕ ( v ) ) , v t = Δ v - u v , is considered in smoothly bounded subdomains of $${\mathbb {R}}^n$$ R n with arbitrary $$n\ge 1$$ n ≥ 1 . Under the assumptions that $$\phi \in C^0([0,\infty )) \cap C^3((0,\infty ))$$ ϕ ∈ C 0 ( [ 0 , ∞ ) ) ∩ C 3 ( ( 0 , ∞ ) ) is positive on $$(0,\infty )$$ ( 0 , ∞ ) and satisfies $$\begin{aligned} \liminf _{\xi \searrow 0} \frac{\phi (\xi )}{\xi ^\alpha }>0 \quad {\text{ and }} \quad \limsup _{\xi \searrow 0} \big \{ \xi ^\beta |\phi '(\xi )| \big \}<\infty \end{aligned}$$ lim inf ξ ↘ 0 ϕ ( ξ ) ξ α > 0 and lim sup ξ ↘ 0 { ξ β | ϕ ′ ( ξ ) | } < ∞ with some $$\alpha >0$$ α > 0 and $$\beta >0$$ β > 0 , for all reasonably regular initial data an associated no-flux type initial-boundary value problem is shown to admit a global solution in an appropriately generalized sense. This extends previously developed solution theories on problems of this form, which either concentrated on non-degenerate or weakly degenerate cases corresponding to the choices $$\alpha =0$$ α = 0 and $$\alpha \in (0,2)$$ α ∈ ( 0 , 2 ) , or were restricted to low-dimensional settings by requiring that $$n\le 2$$ n ≤ 2 .
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Classical solutions to Cauchy problems for parabolic–elliptic systems of Keller-Segel type - Winkler, Michael (Open Mathematics)
Abstract The Cauchy problem in R n {{\mathbb{R}}}^{n} , n ≥ 2 n\ge 2 , for u t = Δ u − ∇ ⋅ ( u S ⋅ ∇ v ) , 0 = Δ v + u , ( ⋆ ) \begin{array}{r}\left\{\phantom{\rule[-1.25em]{}{0ex}}\begin{array}{l}{u}_{t}=\Delta u-\nabla \cdot \left(uS\cdot \nabla v),\\ 0=\Delta v+u,\end{array}\right.\hspace{2.0em}\hspace{2.0em}\hspace{2.0em}\left(\star )\end{array} is considered for general matrices S ∈ R n × n S\in {{\mathbb{R}}}^{n\times n} . A theory of local-in-time classical existence and extensibility is developed in a framework that differs from those considered in large parts of the literature by involving bounded classical solutions. Specifically, it is shown that for all non-negative initial data belonging to BUC ( R n ) ∩ L p ( R n ) {\rm{BUC}}\left({{\mathbb{R}}}^{n})\cap {L}^{p}\left({{\mathbb{R}}}^{n}) with some p ∈ [ 1 , n ) p\in \left[1,n) , there exist T max ∈ ( 0 , ∞ ] {T}_{\max }\in \left(0,\infty ] and a uniquely determined u ∈ C 0 ( [ 0 , T max ) ; BUC ( R n ) ) ∩ C 0 ( [ 0 , T max ) ; L p ( R n ) ) ∩ C ∞ ( R n × ( 0 , T max ) ) u\in {C}^{0}\left(\left[0,{T}_{\max });\hspace{0.33em}{\rm{BUC}}\left({{\mathbb{R}}}^{n}))\cap {C}^{0}\left(\left[0,{T}_{\max });\hspace{0.33em}{L}^{p}\left({{\mathbb{R}}}^{n}))\cap {C}^{\infty }\left({{\mathbb{R}}}^{n}\times \left(0,{T}_{\max })) such that with v ≔ Γ ⋆ u v:= \Gamma \star u , and with Γ \Gamma denoting the Newtonian kernel on R n {{\mathbb{R}}}^{n} , the pair ( u , v ) \left(u,v) forms a classical solution of ( ⋆ \star ) in R n × ( 0 , T max ) {{\mathbb{R}}}^{n}\times \left(0,{T}_{\max }) , which has the property that if T max < ∞ , then both limsup t ↗ T max ‖ u ( ⋅ , t ) ‖ L ∞ ( R n ) = ∞ and limsup t ↗ T max ‖ ∇ v ( ⋅ , t ) ‖ L ∞ ( R n ) = ∞ . \hspace{0.1em}\text{if}\hspace{0.1em}\hspace{0.33em}{T}_{\max }\lt \infty ,\hspace{1.0em}\hspace{0.1em}\text{then both}\hspace{0.1em}\hspace{0.33em}\mathop{\mathrm{limsup}}\limits_{t\nearrow {T}_{\max }}\Vert u\left(\cdot ,t){\Vert }_{{L}^{\infty }\left({{\mathbb{R}}}^{n})}=\infty \hspace{1.0em}\hspace{0.1em}\text{and}\hspace{0.1em}\hspace{1.0em}\mathop{\mathrm{limsup}}\limits_{t\nearrow {T}_{\max }}\Vert \nabla v\left(\cdot ,t){\Vert }_{{L}^{\infty }\left({{\mathbb{R}}}^{n})}=\infty . An exemplary application of this provides a result on global classical solvability in cases when ∣ S + 1 ∣ | S+{\bf{1}}| is sufficiently small, where 1 = diag ( 1 , … , 1 ) {\bf{1}}={\rm{diag}}\hspace{0.33em}\left(1,\ldots ,1) .
Keywords: General Mathematics

Stabilization despite pervasive strong cross-degeneracies in a nonlinear diffusion model for migration–consumption interaction - Winkler, Michael (Nonlinearity)
Abstract A no-flux initial-boundary value problem for <?CDATA \begin{align*} \begin{cases} u_t = \Delta \big(u\phi(v)\big), \\[1mm] v_t = \Delta v-uv, \end{cases} \qquad \qquad (\star) \end{align*}?> <mml:mtable columnalign="right left right left right left right left right left right left" columnspacing="0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em" rowspacing="3pt">ut=Δ(uϕ(v)),vt=Δv−uv,(⋆) is considered in smoothly bounded subdomains of <?CDATA $\mathbb{R}^n$?> Rn with <?CDATA $n\geqslant 1$?> n⩾1 and suitably regular initial data, where φ is assumed to reflect algebraic type cross-degeneracies by sharing essential features with <?CDATA $0\leqslant \xi\mapsto \xi^\alpha$?> 0⩽ξ↦ξα for some <?CDATA $\alpha\geqslant 1$?> α⩾1 . Based on the discovery of a gradient structure acting at regularity levels mild enough to be consistent with degeneracy-driven limitations of smoothness information, in this general setting it is shown that with some measurable limit profile <?CDATA $u_\infty$?> u∞ and some null set <?CDATA $N_\star\subset (0,\infty)$?> N⋆⊂(0,∞) , a corresponding global generalized solution, known to exist according to recent literature, satisfies <?CDATA \begin{align*} \rho(u(\cdot,t))\stackrel{\star}{\rightharpoonup} \rho(u_\infty) \quad \textrm{in } L^\infty(\Omega) \quad\;\; \textrm{ and } \quad\;\; v(\cdot,t)\to 0 \quad \textrm{in } L^p(\Omega)\; \textrm{for all } p\geqslant 1 \end{align*}?> <mml:mtable columnalign="right left right left right left right left right left right left" columnspacing="0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em" rowspacing="3pt">ρ(u(⋅,t))⇀⋆ρ(u∞)in L∞(Ω) and v(⋅,t)→0in Lp(Ω)for all p⩾1 as <?CDATA $(0,\infty)\setminus N_\star \ni t\to \infty$?> (0,∞)∖N⋆∋t→∞ , where <?CDATA $\rho(\xi): = \frac{\xi^2}{(\xi+1)^2}$?> ρ(ξ):=ξ2(ξ+1)2 , <?CDATA $\xi\geqslant 0$?> ξ⩾0 . In the particular case when either <?CDATA $n\leqslant 2$?> n⩽2 and <?CDATA $\alpha\geqslant 1$?> α⩾1 is arbitrary, or <?CDATA $n\geqslant 1$?> n⩾1 and <?CDATA $\alpha\in [1,2]$?> α∈[1,2] , additional quantitative information on the deviation of trajectories from the initial data is derived. This is found to imply a lower estimate for the spatial oscillation of the respective first components throughout evolution, and moreover this is seen to entail that each of the uncountably many steady states <?CDATA $(u_\star,0)$?> (u⋆,0) of ( <?CDATA $\star$?> ⋆ ) is stable with respect to a suitably chosen norm topology.
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Solutions to the Keller–Segel system with non-integrable behavior at spatial infinity - Winkler, Michael (Journal of Elliptic and Parabolic Equations)
Abstract The Cauchy problem in $$\mathbb {R}^n$$ R n is considered for the Keller–Segel system $$\begin{aligned} \left\{ \begin{array}{l}u_t = \Delta u - \nabla \cdot (u\nabla v), \\ 0 = \Delta v + u, \end{array} \right. \qquad \qquad (\star ) \end{aligned}$$ u t = Δ u - ∇ · ( u ∇ v ) , 0 = Δ v + u , ( ⋆ ) with a focus on a detailed description of behavior in the presence of nonnegative radially symmetric initial data $$u_0$$ u 0 with non-integrable behavior at spatial infinity. It is shown that if $$u_0$$ u 0 is continuous and bounded, then ( $$\star $$ ⋆ ) admits a local-in-time classical solution, whereas if $$u_0(x)\rightarrow +\infty $$ u 0 ( x ) → + ∞ as $$|x|\rightarrow \infty $$ | x | → ∞ , then no such solution can be found. Furthermore, a collection of three sufficient criteria for either global existence or global nonexistence indicates that with respect to the occurrence of finite-time blow-up, spatial decay properties of an explicit singular steady state plays a critical role. In particular, this underlines that explosions in ( $$\star $$ ⋆ ) need not be enforced by initially high concentrations near finite points, but can be exclusively due to large tails.
Keywords: Applied Mathematics; Numerical Analysis; Analysis

Keller–Segel–Stokes interaction involving signal‐dependent motilities - Tian, Yu; Winkler, Michael (Mathematical Methods in the Applied Sciences)
The chemotaxis‐Stokes system is considered along with homogeneous boundary conditions of no‐flux type for and , and of Dirichlet type for , in a smoothly bounded domain . Under the assumption that , that is bounded on each of the intervals with arbitrary , and that with some and , we have It is shown that for any suitably regular initial data, an associated initial‐boundary value problem admits a global very weak solution.
Keywords: General Engineering; General Mathematics

Depleting the signal: Analysis of chemotaxis‐consumption models—A survey - Lankeit, Johannes; Winkler, Michael (Studies in Applied Mathematics)
Abstract We give an overview of analytical results concerned with chemotaxis systems where the signal is absorbed. We recall results on existence and properties of solutions for the prototypical chemotaxis‐consumption model and various variants and review more recent findings on its ability to support the emergence of spatial structures.
Keywords: Applied Mathematics

Phenotype Switching in Chemotaxis Aggregation Models Controls the Spontaneous Emergence of Large Densities - Painter, Kevin J.; Winkler, Michael (SIAM Journal on Applied Mathematics)
Keywords: Applied Mathematics

Avoiding critical mass phenomena by arbitrarily mild saturation of cross-diffusive fluxes in two-dimensional Keller-Segel-Navier-Stokes systems - Winkler, Michael; Yokota, Tomomi (Journal of Differential Equations)
Keywords: Analysis; Applied Mathematics

Absence of collapse into persistent Dirac-type singularities in a Keller-Segel-Navier-Stokes system involving local sensing - Winkler, Michael (Advances in Differential Equations)
Keywords: Applied Mathematics; Analysis

A Viewpoint on Human Factors in Software Supply Chain Security: A Research Agenda - Fourné, Marcel; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (IEEE Secur. Priv.)

Turnover-Based Corporate Income Taxation and Corporate Risk-Taking - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

"We’ve Disabled MFA for You": An Evaluation of the Security and Usability of Multi-Factor Authentication Recovery Deployments - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Krause, Alexander; Simko, Lucy; Acar, Yasemin; Fahl, Sascha (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security, CCS 2023, Copenhagen, Denmark, November 26-30, 2023)

Security, Privacy, and Data-sharing Trade-offs When Moving to the United States: Insights from a Qualitative Study - Tran, Mindy; Munyendo, Collins W; Sri Ramulu, Harshini; Rodriguez, Rachel Gonzalez; Schnell, Luisa Ball; Sula, Cora; Simko, Lucy; Acar, Yasemin (2024 IEEE Symposium on Security and Privacy (SP))

"We’ve Disabled MFA for You": An Evaluation of the Security and Usability of Multi-Factor Authentication Recovery Deployments - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Krause, Alexander; Simko, Lucy; Acar, Yasemin; Fahl, Sascha (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)

A Viewpoint on Human Factors in Software Supply Chain Security: A Research Agenda - Fourné, Marcel; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (IEEE Security & Privacy)

The Use and Non-Use of Technology During Hurricanes - Simko, Lucy; Sri Ramulu, Harshini; Kohno, Tadayoshi; Acar, Yasemin (Proc. ACM Hum. Comput. Interact.)

"Oh yes! over-preparing for meetings is my jam :)": The Gendered Experiences of System Administrators - Kaur, Mannat; Sri Ramulu, Harshini; Acar, Yasemin; Fiebig, Tobias (Proc. ACM Hum. Comput. Interact.)

Neue Wege im mathematischen Unterricht: Auf den Spuren Mathilde Vaertings - Werth, Gerda

Standardkonstruktionen eigenständig entdecken. Mathilde Vaertings Idee der Selbstständigkeitsprobe - Werth, Gerda (mathematik lehren)

Bruchmechanische Untersuchung des Dualphasenstahls HCT590X unter Temperatureinfluss - Weiß, Deborah; Duffe, Tobias; Buczek, Moritz; Kullmer, Gunter; Schramm, Britta

CLIL - Content and Language Integrated Learning - Böttger, Lydia; Niederhaus, Constanze (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis. Ein Handbuch aus DaF- und DaZ Perspektive)

$L^2$-spectrum, growth indicator function and critical exponent on locally symmetric spaces - Wolf, Lasse L.; Zhang, Hong-Wei (arXiv:2311.11770)
In this short note we observe, on locally symmetric spaces of higher rank, a connection between the growth indicator function introduced by Quint and the modified critical exponent of the Poincar\'e series equipped with the polyhedral distance. As a consequence, we provide a different characterization of the bottom of the $L^2$-spectrum of the Laplace-Beltrami operator in terms of the growth indicator function. Moreover, we explore the relationship between these three objects and the temperedness.

Design-Based Research als Erforschung und Gestaltung von Interaktionsprozessen zwischen Wissenschaft und Bildungspraxis - Jenert, Tobias (Wissenschaft trifft Praxis – Designbasierte Forschung in der beruflichen Bildung)
Das Verhältnis zwischen Wissenschaft und Praxis wurde in unterschiedlichen Forschungsansätzen im- mer wieder wissenschaftlich betrachtet. Dennoch ist es notwendig, sich im Rahmen der wissenschafts- theoretischen Konzeption von Design-Based Research (DBR) weiter damit auseinanderzusetzen, denn Interaktion zwischen Wissenschaft und Bildungspraxis ist ein zentrales Merkmal von DBR. Dieser Beitrag befasst sich mit der Frage, wie sich diese Interaktion je nach zugrunde liegendem DBR-Verständnis me- thodologisch fassen lässt. Die Interaktion wird als ein wesentlicher Bestandteil des Erkenntnisprozesses in DBR aufgefasst. Daher wird neben der methodischen Ausgestaltung von Interaktionsprozessen auch methodologisch reflektiert, was die Wissenschaft-Praxis-Interaktion für die Erkenntnis an sich bedeutet.

JuGaze: A Cell-based Eye Tracking and Logging Tool for Jupyter Notebooks - Sparmann, Sören; Hüsing, Sven; Schulte, Carsten (Proceedings of the 23rd Koli Calling International Conference on Computing Education Research)

Resonances and Weighted Zeta Functions for Obstacle Scattering via Smooth Models - Delarue, Benjamin; Schütte, Philipp; Weich, Tobias (Annales Henri Poincaré)
Abstract We consider a geodesic billiard system consisting of a complete Riemannian manifold and an obstacle submanifold with boundary at which the trajectories of the geodesic flow experience specular reflections. We show that if the geodesic billiard system is hyperbolic on its trapped set and the latter is compact and non-grazing, the techniques for open hyperbolic systems developed by Dyatlov and Guillarmou (Ann Henri Poincaré 17(11):3089–3146, 2016) can be applied to a smooth model for the discontinuous flow defined by the non-grazing billiard trajectories. This allows us to obtain a meromorphic resolvent for the generator of the billiard flow. As an application we prove a meromorphic continuation of weighted zeta functions together with explicit residue formulae. In particular, our results apply to scattering by convex obstacles in the Euclidean plane.
Keywords: Mathematical Physics; Nuclear and High Energy Physics; Statistical and Nonlinear Physics

Singular cohomology of symplectic quotients by circle actions and Kirwan surjectivity - Delarue, Benjamin; Ramacher, Pablo; Schmitt, Maximilian (arXiv:2312.03634)
Let $M$ be a symplectic manifold carrying a Hamiltonian $S^1$-action with momentum map $J:M → \mathbb{R}$ and consider the corresponding symplectic quotient $\mathcal{M}_0:=J^{-1}(0)/S^1$. We extend Sjamaar's complex of differential forms on $\mathcal{M}_0$, whose cohomology is isomorphic to the singular cohomology $H(\mathcal{M}_0;\mathbb{R})$ of $\mathcal{M}_0$ with real coefficients, to a complex of differential forms on $\mathcal{M}_0$ associated with a partial desingularization $\widetilde{\mathcal{M}}_0$, which we call resolution differential forms. The cohomology of that complex turns out to be isomorphic to the de Rham cohomology $H(\widetilde{ \mathcal{M}}_0)$ of $\widetilde{\mathcal{M}}_0$. Based on this, we derive a long exact sequence involving both $H(\mathcal{M}_0;\mathbb{R})$ and $H(\widetilde{ \mathcal{M}}_0)$ and give conditions for its splitting. We then define a Kirwan map $\mathcal{K}:H_{S^1}(M) → H(\widetilde{\mathcal{M}}_0)$ from the equivariant cohomology $H_{S^1}(M)$ of $M$ to $H(\widetilde{\mathcal{M}}_0)$ and show that its image contains the image of $H(\mathcal{M}_0;\mathbb{R})$ in $H(\widetilde{\mathcal{M}}_0)$ under the natural inclusion. Combining both results in the case that all fixed point components of $M$ have vanishing odd cohomology we obtain a surjection $\check κ:H^ev_{S^1}(M) → H^ev(\mathcal{M}_0;\mathbb{R})$ in even degrees, while already simple examples show that a similar surjection in odd degrees does not exist in general. As an interesting class of examples we study abelian polygon spaces.

A Riemann-Roch formula for singular reductions by circle actions - Delarue, Benjamin; Ioos, Louis; Ramacher, Pablo (arXiv:2302.09894)
We compute a Riemann-Roch formula for the invariant Riemann-Roch number of a quantizable Hamiltonian $S^1$-manifold $(M,ω,\mathcal{J})$ in terms of the geometry of its symplectic quotient, allowing $0$ to be a singular value of the moment map $\mathcal{J}:M→\mathbb{R}$. The formula involves a new explicit local invariant of the singularities. Our approach relies on a complete singular stationary phase expansion of the associated Witten integral.

Das Projekt "Schule für Alle" der Universität Bielefeld: ein Mentoring-Projekt mit rassismuskritischen Ansätzen in Deutschland - Pieper, Catania; Kottmann, Brigitte; Reh, Anne (Mentoring-Projekt für Roma-Kinder in Europa)

Demo: Chat based Emergency Service via Long Range Wireless Communication (LoRa) - Stiballe, Alisa; Welzel, Simon; Dorfschmidt, Johannes; Schluter, Darvin; Steuter, Dominik Delgado; Hense, Jannik Lukas; Klingler, Florian (2023 IEEE 48th Conference on Local Computer Networks (LCN))

Low Earth Orbit Satellite Supported Multi-Hop Dissemination of Messages in V2X Networks - Franke, Mario; Stroop, Roland; Klingler, Florian; Sommer, Christoph (2023 IEEE 97th Vehicular Technology Conference (VTC2023-Spring))

Ingo Schulze und Frank Witzel im Dialog. Die 40. Paderborner Gastdozentur für Schriftsteller und Schriftstellerinnen und das sie begleitende wissenschaftliche Symposium. In: Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren „Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller“ - Eke, Norbert Otto; Elit, Stefan (Zeitschrift für deutsche Philologie)

Virtuelle Begegnungen. Nach vier Jahrzehnten Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller. In: Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren „Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller“ - Eke, Norbert Otto; Elit, Stefan (Zeitschrift für deutsche Philologie)

Geleitwort. In: Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren „Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller“ - Eke, Norbert; Elit, Stefan (Zeitschrift für deutsche Philologie)

Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren „Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller“ (Zeitschrift für deutsche Philologie)

Handbuch Versepik

[Klopstocks] Sprachtheoretische Schriften - Elit, Stefan (Klopstock-Handbuch. Leben – Werk – Wirkung)

[Klopstocks] Liebe und Freundschaft - Elit, Stefan (Klopstock-Handbuch. Leben – Werk – Wirkung)

Coupled CP Tensor Decomposition with Shared and Distinct Components for Multi-Task Fmri Data Fusion - Borsoi, R. A.; Lehmann, Isabell; Akhonda, M. A. B. S.; Calhoun, V. D.; Usevich, K.; Brie, D.; Adali, T. (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Deriving 3D Functional Brain Regions from Multi-Slice Functional Ultrasound Data Using ICA and IVA - Lehmann, Isabell; Adali, Tülay; Kruizinga, Pieter; Hunyadi, Borbála (2023 57th Asilomar Conference on Signals, Systems, and Computers)

Einleitung - Elit, Stefan; Bremer, Kai (Handbuch Versepik)

‚[M]uch too terrible for representation‘. Musik und Geräusch in Matthew Lewis’ Melodram The Captive (1803) - Ricke, Anna (Musik und das Unheimliche)

Flexibilitätsgeprägte Biographien als methodische Herausforderung – Das Beispiel der Musikerin Smaragda Eger-Berg - Ricke, Anna (Kulturelles Handeln | Macht | Mobil. Interdisziplinäre Studien zur gender- und musikbezogenen Mobilitätsforschung)

Musikwelten der Wiener Moderne. Das Beispiel der künstlerischen Emanzipation der Musikerin Smaragda Eger-Berg - Ricke, Anna (It's a Man's World? Künstlerinnen in Europas Musik-Metropolen des frühen 20. Jahrhunderts)

An interval multi-criteria decision-making model for evaluating blockchain-IoT technology in supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Ahmadabadi, Alireza Barati; Amiri, Alireza Shamekhi; Mina, Hassan (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Analytic hierarchy process and data envelopment analysis: A match made in heaven - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

A bi-objective hybrid vibration damping optimization model for synchronous flow shop scheduling problems - Tavana, Madjid; Hajipour, Vahid; Alaghebandha, Mohammad; Di Caprio, Debora (Machine Learning with Applications)
Keywords: General Medicine

A general Best-Worst method considering interdependency with application to innovation and technology assessment at NASA - Tavana, Madjid; Mina, Hassan; Santos-Arteaga, Francisco J. (Journal of Business Research)
Keywords: Marketing

Analytical hierarchy process: revolution and evolution - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J. (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A fuzzy preference programming and weighted influence non-linear gauge system for mission architecture assessment at NASA - Tavana, Madjid; Heidary, Mohammad Saeed; Mina, Hassan (Applied Soft Computing)
Keywords: Software

A Credibility and Strategic Behavior Approach in Hesitant Multiple Criteria Decision-Making With Application to Sustainable Transportation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; Tena, Emilio Cerda (IEEE Transactions on Fuzzy Systems)
Keywords: Applied Mathematics; Artificial Intelligence; Computational Theory and Mathematics; Control and Systems Engineering

Value Chain digitalization and technological development as innovation catalysts in small and medium-sized enterprises - Marín, Raquel; Santos-Arteaga, Francisco J.; Tavana, Madjid; Di Caprio, Debora (Journal of Innovation & Knowledge)
Keywords: Management of Technology and Innovation; Marketing; Economics and Econometrics; Business and International Management

An integrated decision support framework for resilient vaccine supply chain network design - Tirkolaee, Erfan Babaee; Torkayesh, Ali Ebadi; Tavana, Madjid; Goli, Alireza; Simic, Vladimir; Ding, Weiping (Engineering Applications of Artificial Intelligence)
Keywords: Electrical and Electronic Engineering; Artificial Intelligence; Control and Systems Engineering

A hybrid multi-attribute decision-making and data envelopment analysis model with heterogeneous attributes: The case of sustainable development goals - Soltanifar, Mehdi; Tavana, Madjid; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Environmental Science & Policy)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Spacecraft tracking control and synchronization: An assessment of conventional, unconventional, and combined methods - Deveci, Muhammet; Pamucar, Dragan; Gokasar, Ilgin; Tavana, Madjid (Advances in Space Research)
Keywords: Space and Planetary Science; Aerospace Engineering; General Earth and Planetary Sciences; Atmospheric Science; Geophysics; Astronomy and Astrophysics

A novel median-based optimization model for eco-efficiency assessment in data envelopment analysis - Dellnitz, Andreas; Tavana, Madjid; Banker, Rajiv (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A combinatorial data envelopment analysis with uncertain interval data with application to ICT evaluation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid (Technological Forecasting and Social Change)
Keywords: Management of Technology and Innovation; Applied Psychology; Business and International Management

A novel indicator for sustainability in production planning using Center of Gravity-based assessment of Pareto fronts - Hilbert, Markus; Dellnitz, Andreas; Kleine, Andreas; Tavana, Madjid (Computers & Industrial Engineering)
Keywords: General Engineering; General Computer Science

From classical interpretive structural modeling to total interpretive structural modeling and beyond: A half-century of business research - Sorooshian, Shahryar; Tavana, Madjid; Ribeiro-Navarrete, Samuel (Journal of Business Research)
Keywords: Marketing

A new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps - Namazi, Mehdi; Tavana, Madjid; Mohammadi, Emran; Bonyadi Naeini, Ali (Benchmarking: An International Journal)
Purpose New business practices and the globalization of markets force firms to take innovation as the fundamental pillar of their competitive strategy. Research and Development (R&D) plays a vital role in innovation. As technology advances and product life cycles become shorter, firms rely on R&D as a strategy to invigorate innovation. R&D project portfolio selection is a complex and challenging task. Despite the management's efforts to implement the best project portfolio selection practices, many projects continue to fail or miss their target. The problem is that selecting R&D projects requires a deep understanding of strategic vision and technical capabilities. However, many decision-makers lack technological insight or strategic vision. This article aims to provide a method to capitalize on the expertise of R&D professionals to assist managers in making informed and effective decisions. It also provides a framework for aligning the portfolio of R&D projects with the organizational vision and mission. Design/methodology/approach This article proposes a new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps. Findings The proposed strategy plane helps decision-makers align R&D project portfolios with their strategies to combine a strategic view and numerical analysis in this research. The proposed strategy plane consists of four areas: Exploitation Zone, Challenge Zone, Desperation Zone and Discretion Zone. Mapping the project into this strategic plane would help decision-makers align their project portfolio according to the corporate perspectives. Originality/value The new approach combines the efficiency and uncertainty dimensions in portfolio selection into an integrated framework that: (i) provides a complete representation of the stochastic decision-making processes, (ii) models the endogenous uncertainty inherent in the project selection process and (iii) proposes a computationally practical and visually unique solution procedure for classifying desirable and undesirable R&D projects.
Keywords: Business and International Management; Strategy and Management

A comparative performance analysis of intelligence-based algorithms for optimizing competitive facility location problems - Hajipour, Vahid; Niaki, Seyed Taghi Akhavan; Tavana, Madjid; Santos-Arteaga, Francisco J.; Hosseinzadeh, Sanaz (Machine Learning with Applications)
Keywords: General Medicine

A Game-Theoretic Framework for Analyzing the Impact of Social Responsibility and Supply Chain Profitability - Mahdiraji, Hannan Amoozad; Tavana, Madjid; Rezayar, Ali (Cybernetics and Systems)
Keywords: Artificial Intelligence; Information Systems; Software

Business Reputation Systems based on Blockchain Technology—A Risky Advance - Hemmrich, Simon (Proceedings of 31st European Conference on Information Systems (ECIS 2023))
Reputation is indispensable for online business since it supports customers in their buying decisions and allows sellers to justify premium prices. While IS research has investigated reputation systems mainly as review systems on online platforms for business-to-consumer (B2C) transactions, no proper solutions have been developed for business-to-business (B2B) transactions yet. We use blockchain technology to propose a new class of reputation systems that apply ratings as voluntary bonus payments: Before a transaction is performed, customers commit to pay a bonus that is granted if a service provider has performed a service properly. As opposed to rival reputation systems that build on cumulated ratings or reviews, our system enables monetized reputation mechanisms that are inextricably linked with online transactions. We expect this system class to provide more trustworthy ratings, which might reduce agency costs and serve quality providers to establish a reputation towards new customers, building on second-order trust.
Keywords: Trust; Risk; Reputation System; Blockchain Technology; Business Reputation System.

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Scalable Multi-FPGA Design of a Discontinuous Galerkin Shallow-Water Model on Unstructured Meshes - Faj, Jennifer; Kenter, Tobias; Faghih-Naini, Sara; Plessl, Christian; Aizinger, Vadym (Proceedings of the Platform for Advanced Scientific Computing Conference (PASC))

FPGA Acceleration for HPC Supercapacitor Simulations - Prouveur, Charles; Haefele, Matthieu; Kenter, Tobias; Voss, Nils (Proceedings of the Platform for Advanced Scientific Computing Conference (PASC))

Asymptotic Behavior of the Heat Semigroup on Certain Riemannian Manifolds - Grigor'yan, Alexander; Papageorgiou, Efthymia; Zhang, Hong-Wei (From Classical Analysis to Analysis on Fractals. A Tribute to Robert Strichartz, Volume 1)

Large-Time Behavior of Two Families of Operators Related to the Fractional Laplacian on Certain Riemannian Manifolds - Papageorgiou, Efthymia (Potential Analysis)
Abstract This note is concerned with two families of operators related to the fractional Laplacian, the first arising from the Caffarelli-Silvestre extension problem and the second from the fractional heat equation. They both include the Poisson semigroup. We show that on a complete, connected, and non-compact Riemannian manifold of non-negative Ricci curvature, in both cases, the solution with $$L^1$$ L 1 initial data behaves asymptotically as the mass times the fundamental solution. Similar long-time convergence results remain valid on more general manifolds satisfying the Li-Yau two-sided estimate of the heat kernel. The situation changes drastically on hyperbolic space, and more generally on rank one non-compact symmetric spaces: we show that for the Poisson semigroup, the convergence to the Poisson kernel fails -but remains true under the additional assumption of radial initial data.
Keywords: Analysis

Asymptotics for the infinite Brownian loop on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Elliptic and Parabolic Equations)
Abstract The infinite Brownian loop on a Riemannian manifold is the limit in distribution of the Brownian bridge of length T around a fixed origin when $$T → +∞ $$ T → + ∞ . The aim of this note is to study its long-time asymptotics on Riemannian symmetric spaces G / K of noncompact type and of general rank. This amounts to the behavior of solutions to the heat equation subject to the Doob transform induced by the ground spherical function. Unlike the standard Brownian motion, we observe in this case phenomena which are similar to the Euclidean setting, namely $$L^1$$ L 1 asymptotic convergence without requiring bi- K -invariance for initial data, and strong $$L^{∞ }$$ L ∞ convergence.
Keywords: Applied Mathematics; Numerical Analysis; Analysis

New examples of harmonic maps to the hyperbolic plane via Bäcklund transformation - Polychrou, G.; Papageorgiou, Efthymia; Fotiadis, A.; Daskaloyannis, C. (Revista Matemática Complutense)
Abstract We study harmonic maps from a subset of the complex plane to a subset of the hyperbolic plane. In Fotiadis and Daskaloyannis (Nonlinear Anal 214, 112546, 2022), harmonic maps are related to the sinh-Gordon equation and a Bäcklund transformation is introduced, which connects solutions of the sinh-Gordon and sine-Gordon equation. We develop this machinery in order to construct new harmonic maps to the hyperbolic plane.
Keywords: General Mathematics

Privacy-centered authentication: A new framework and analysis - Robles-González, Antonio; Arias Cabarcos, Patricia; Parra-Arnau, Javier (Computers & Security)
Keywords: Law; General Computer Science

Overcoming Theory: Designing Brainwave Authentication for the Real World - Röse, Markus; Kablo, Emiram; Arias Cabarcos, Patricia (Proceedings of the 2023 European Symposium on Usable Security)

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André

Reducing Contact Bouncing of a Relay by Optimizing the Switch Signal During Run-Time - Winkel, Fabian; Scholz, Peter; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Automation Science and Engineering)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

The composition of pre-service teacher teams and children’s competencies in inclusive education. 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva